KEMAMPUAN GURU KELAS RENDAH SD NEGERI 43 KOTA TERNATE DALAM MERANCANG DAN MELAKSANAKAN PEMBELAJARAN TEMATIK - Sanape, Yulensi; Somadayo, Samsu; Srinawati, Risna (Prodi PGSD FKIP Universitas Khairun, 2024)
The aim of this research is to determine and describe teachers' abilities in planning learning and the abilities of lower grade teachers in implementing thematic learning at SD Negeri 43 Ternate City. The research method used in this research is qualitative description, data was obtained using observation, interview and documentation techniques with data analysis techniques, namely data collection, data reduction, presentation of conclusion data. The results of the research show that in preparing learning tools teachers are still confused about formulating indicators for achieving basic competencies in achieving learning goals. Meanwhile, in implementing thematic learning, teachers encounter obstacles because students do not yet understand the transition from one subject to another, so that the learning objectives have not been achieved optimally. Evaluation of the thematic learning implementation plan is carried out on students and teachers, so that students can find out individual abilities in the class, in this case assessing students in writing and giving assignments to determine student achievement in learning objectives and for teachers to know whether a teacher is successful or not in the learning process the teacher makes observations during the learning process.